Wheat Cost-Return Budget (W-S-F Rotation) in Western Kansas - O'Brien, Daniel M.; Dumler, Troy J. (My University, 1999)
This publication projects a budget that reflects expected income and costs based on typical production of wheat in western Kansas.
MF903_1999_10
Keywords: MF907; Economics; Crops; MF